Penerapan Modul Surya sebagai Receiver Sistem Visible Light Communication (VLC) untuk Pengiriman Sinyal Audio - Budiyawan Naztin; Tri Nopiani Damayanti; Sugondo Hadiyoso (Jurnal Rekayasa Elektrika, 2018)
A solar module as a collector of sunlight that will be converted into electrical energy, so far only used for various applications of renewable energy technology. This research proposes and demonstrates the application of solar module as receiver of Visible Light  Communication System (VLC) as well as collecting energy at the same time. Using a solar module as a receiver causes the receiver does not require an external voltage source. This study tested the acoustic audio signal transmitted through the VLC system to be received by the solar module as a receiver. The results show that the transmitted audio signal has a signal change as a result of the magnitude/amplitude whose value changes with time. The change of voltage level over time causes the LED emission to have different light intensity. Maximum distance of the signal can be transmitted well at a distance of 120 cm at 656 mV voltage with a light intensity of environmental lighting test of 265 Lx. The maximum angle of the signal can be transmitted well at an angle of 20o at a voltage of 190 mV with a light intensity of the test environment light of 265 Lx. The change in voltage values is affected by the LED emission and the light intensity of the test environment light received by the solar module as a receiver. Testing indicates that the audio signal remains well transmitted even though the light energy received by the solar module is in maximum condition.